2015
DOI: 10.1002/jbt.21730
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxy-d-Glucose Sensitizes Human Ovarian Cancer Cells to Cisplatin by Increasing ER Stress and Decreasing ATP Stores in Acidic Vesicles

Abstract: Cisplatin is a commonly used chemotherapeutic agent; however, the development of acquired resistance limits its application. Here, we demonstrate that 2-deoxy-d-glucose (2-DG) enhanced the antitumor effects of cisplatin in SKOV3 cells, which include inhibition of proliferation and promotion of apoptosis. Additionally, either cisplatin or 2-DG alone could upregulate the endoplasmic reticulum (ER) stress-associated protein glucose-regulated protein-78 (GRP78). Moreover, exposure to 2-DG increased the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Tumor glycolysis is regarded as a target for cancer therapy (38), and experimental data show that the inhibition of glycolysis enhances cisplatin-induced apoptosis in ovarian cancer cells (39). Because our findings showed that earlier exposure to S1 mainly reduces mitochondrial respiration and that the upregulation of glycolysis seemed to be a compensatory effect, we speculated that the glycolysis inhibitor 2-DG would further aggravate the apoptosis induced by S1.…”
Section: Discussionmentioning
confidence: 78%
“…Tumor glycolysis is regarded as a target for cancer therapy (38), and experimental data show that the inhibition of glycolysis enhances cisplatin-induced apoptosis in ovarian cancer cells (39). Because our findings showed that earlier exposure to S1 mainly reduces mitochondrial respiration and that the upregulation of glycolysis seemed to be a compensatory effect, we speculated that the glycolysis inhibitor 2-DG would further aggravate the apoptosis induced by S1.…”
Section: Discussionmentioning
confidence: 78%
“…The intracellular accumulation of this metabolite inhibits hexokinase activity and therefore ATP production via glycolysis. Significantly, the anti-proliferative effects of 2-DG have been demonstrated in numerous preclinical studies (Giammarioli et al, 2012;Zhang et al, 2015). 2-DG has also been shown to be an effective sensitizer in several tumor types, including gliomas and lung carcinomas (Dwarkanath et al, 2001;Singh et al, 2019).…”
Section: The Role Of Metabolic Reprogramming In Tumor Cell Chemo-and mentioning
confidence: 99%
“…Additionally, combining 2-DG with chemotherapy has already shown promising results in its ability to restore the sensitivity of chemo-resistance cells. A recent study analyzed the effect of combination treatment with 2-DG and carboplatin chemotherapy in high stage and recurrent ovarian clear cell carcinoma (OCC), and found that 2-DG in combination with carboplatin and cisplatin chemotherapy increased efficacy in chemo-resistant ovarian tumor cell lines and patient-derived xenograft models (Zhang et al, 2015;Khan et al, 2020). Thus, the combination of 2-DG with both radio-and chemotherapy drugs improves tumor cell sensitivity; however, the underlying mechanism for the restoration of sensitivity to therapy remains largely unknown.…”
Section: The Role Of Metabolic Reprogramming In Tumor Cell Chemo-and mentioning
confidence: 99%
“…The present work aims to improve the insight into Golgi apparatus dynamics and unravel processes of Golgi apparatus disorganizations and reorganizations. For this, we used 2-deoxy- d -glucose (2DG), a nonmetabolizable glucose analogue, which causes a reversible decrease of the cellular levels of adenosine triphosphate (ATP) and which is used in both experimental cell biology and medicine (e.g., Aft et al 2002; Dwarakanath 2009; Kavaliauskiene et al 2015; Zhang et al 2015). Since the Golgi apparatus changes its architecture under the influence of 2DG, this drug was found to be of great value in the context of Golgi apparatus research (del Valle et al 1999; Meisslitzer-Ruppitsch et al 2011; Ranftler et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 2DG has been found to enhance autophagy, or have discriminating effects on autophagy regulation (Wu et al 2009; Wang et al 2011; Xi et al 2011; Jeon et al 2015), another fact that is of particular interest in anti-tumor-application. The combined use of 2DG and cytostatic drugs and other substances offers promising new possibilities in tumor therapies (Estañ et al 2012; Huang et al 2013; Mustafa et al 2015; Oladghaffari et al 2015; Li et al 2015; Jangamreddy et al 2015; Zhang et al 2015). 2DG might also help in the treatment of systemic lupus erythematodes by normalizing the T cell metabolism (Yin et al 2015) and has been recognized as a caloric restriction mimetic (Ingram and Roth 2015).…”
Section: Introductionmentioning
confidence: 99%